Pengaruh Brand Recognition, Attitude dan confidence Terhadap Minat Beli Konsumen Pada Layanan Online Traveloka (Studi Kasus Pada Mahasiswa Universitas Brawijaya Malang) - Meidiangga Setywan (Jurnal Ilmiah Mahasiswa FEB, 2015)
The goal of this research is to examining factors which influence the people’s ineterest on using traveloka online service. This research is using explanatory research model combined with nonprobabilty sampling as a method and insidental sampling for the technique. Moreover,the result of this research processed by Partial  Least Square  (PLS).   Furthermore,  the  research  participated  by  120 student    of  Brawijaya University  in  Malang  who  yet  using Traveloka  online service. The result of this research describes that the interest of using Traveloka online  service  positively     influenced by  several  variables  such  as brand recognition, attitude, and confidence. The result also shows that it has two main variables which are attitude that influence the people’s interest of using Traveloka and  brand  recognition that  influence the people’s  interest  of  using Traveloka through attitude. In conclusion, the implications of this research  are relevant for Traveloka’s management to focus on and creating marketing strategy based on this research.Keyword: Brand recognition, Atitude, Confidence, Online Service